A Blinding Headache Falling on Deaf Ears (Susac's Syndrome). Issue 6 (1st December 2002) - Fialho, Doreen; Holmes, Paul; Riordan-Eva, Paul; Silber, Eli
Abstract : THE STORY A 23-year-old women, who had just completed a degree in adventure tourism at university and started working as a video librarian, presented with a 6-week history of a throbbing bi-frontal headache, nausea, photophobia and increasing confusion. She had been getting lost even in her own flat and was found outside wandering about aimlessly. Her family commented that her gait was unsteady and her speech had become slurred. The patient's past medical history was unremarkable apart from mild asthma treated with inhalers when required. There was no history of foreign travel, recent illness, vaccinations, alcohol or drug misuse. THE EXAMINATION AND INVESTIGATIONS On admission she was found to be encephalopathic with drowsiness, cognitive impairment [Mini Mental State Examination (MMSE) = 13/30] and cerebellar signs, in particular lateral gaze evoked nystagmus, dysarthria and an ataxic gait. She had myoclonus. Initial blood tests, including ESR, CRP, autoimmune profile, ANCA, dsDNA and